(untitled) (Review Journal of Neurological & Medical Sciences Review, 2025)
Acetylcholinesterase ester enzyme (AChE) is actually a major enzymatic target for numerous therapeutic drugs, playing a pivotal role in Alzheimer’s disease. Researchers are developing new drugs and other strategies to treat this disease. Acetylcholinesterase ester enzyme (AChE) inhibitors (ChEIs) are the primary treatment for Alzheimer’s Disease. These drugs work by slowing Ach turnover, mitigating the effects of cholinergic neuron degeneration, and enhancing synaptic transmission. This review is conducted from the literature published from 1990 to 2024. Research work on human settings is needed to be addressed for authentication of Alzheimer Disease. Hence published data in this review confirms that Acetylcholinesterase ester enzyme. This review examines literature published from 1990 to 2024, highlighting recent advancements in AChE-targeted therapies. While substantial progress has been made, further research in human setting is necessary to validate the therapeutic efficacy of AChE inhibitors in Alzheimer’s disease. The findings presented in this review confirm the significance of AChE as a central target in AD treatment and emphasize the need for continued investigation. Additionally, recent studies have explored the potential of natural compounds and synthetic derivatives as a novel AChE inhibitor, aiming to enhance drug efficacy and reduce side effects. Advancements in AI-driven drug discovery and computational modeling have also contributed to identifying promising AChE-targeted candidates. These developments underscore the ongoing efforts to improve therapeutic strategies for Alzheimer’s disease. Keywords: Acetylcholinesterase (AChE), Alzheimer’s Disease, AChE Inhibitors, Cholinergic Neurotransmission, Multi-target Drug Design, Neurodegenerative Disorders